2013
DOI: 10.1111/ctr.12097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mycophenolate mofetil introduction in liver transplant patients: results from an observational, non‐interventional, multicenter study (LOBSTER)

Abstract: The benefits of calcineurin inhibitor (CNI)-sparing regimens on renal function following liver transplantation (LT) have been demonstrated in clinical studies. This observational study assessed the real-life effects of mycophenolate mofetil (MMF) introduction in LT patients. Four hundred and ninety-seven patients in whom MMF was introduced according to local standards or clinical considerations were entered. Patients were grouped by time between transplantation and start of MMF (start of study): Group A (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…There was significant improvement in eGFR over a 1 year follow-up period in the MMF and low dose CNI arm, without episodes of rejection. Furthermore, two other observational studies demonstrated significant GFR increases with conversion from standard CNI to reduced-dose CNI + MMF without adverse events (67, 70). The main benefit of this CNI reduction strategy was seen in applying this regimen within 1–2 years of LT.…”
Section: Key Points and Recommendationsmentioning
confidence: 94%
See 3 more Smart Citations
“…There was significant improvement in eGFR over a 1 year follow-up period in the MMF and low dose CNI arm, without episodes of rejection. Furthermore, two other observational studies demonstrated significant GFR increases with conversion from standard CNI to reduced-dose CNI + MMF without adverse events (67, 70). The main benefit of this CNI reduction strategy was seen in applying this regimen within 1–2 years of LT.…”
Section: Key Points and Recommendationsmentioning
confidence: 94%
“…Despite evidence of using mTOR-I and MMF early after LT to minimize CNI nephrotoxicity, this strategy does not seem to equally apply later after LT (6370). The trials examining these proposed renal sparing regimens to date are either prospective uncontrolled trials, controlled trials with small sample sizes or retrospective observational studies.…”
Section: Key Points and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ein Wechsel der Immunsuppression von einem CNI-basierten Schema zu mTOR-Inhibitoren (Sirolimus, Everolimus) oder Mycophenolat-Mofetil (MMF) scheint zu einer Verbesserung der Nierenfunktion zu führen und wird aktuell in klinischen Studien untersucht (z. B. HEPHAISTOS-Studie, ClinicalTrials.gov Identifier: NCT01551212) [57,58].…”
Section: Akutes Und Chronisches Nierenversagen Nach Lebertransplantationunclassified